New Syllabus Primary Mathematics - Level 1B - Yee P. Foong (Karachi : Oxford University Press, 2019)
New Syllabus Primary Mathematics (NSPM) is a comprehensive series of textbooks and workbooks that adopts the Concrete-Pictorial-Abstract approach. The (C-P-A) approach forms an integral part of the learning process. NSPM incorporates the use of concrete aids and manipulatives. It is specially written to reflect a student-centered approach, which serves to engage pupils so that they have a solid foundation in Mathematics.
Location : 1B
Keywords: Textbook